2019
DOI: 10.1002/jcop.22235
|View full text |Cite
|
Sign up to set email alerts
|

South African adult caregivers as “protective shields”: Serving as a buffer between stressful neighborhood conditions and youth risk behaviors

Abstract: Low‐income youths in KwaZulu‐Natal, South Africa, face elevated risks to their well‐being from exposure to neighborhood conditions correlated with engaging in risky behaviors. These risks can be mitigated through adult caregivers who serve as protective shields, buffering adverse conditions. However, this protective role is dependent on the caregivers’ mental health and well‐being. This secondary analysis uses baseline data from 475 child‐caregiver dyads in an HIV‐prevention program to examine the mediating ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…It has been shown that children's depression and resilience are causally related to their caregivers' or parents' behavior in HIV-affected families. The more parents are mentally or physically ill, the more children become vulnerable to anxiety, depression, and highrisk behaviors [31,32]. This may lead to poor school performance, concentration issues, and general school failures [23,42,52]; (c) What, if any, psychological interventions have been conducted for HEU children?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that children's depression and resilience are causally related to their caregivers' or parents' behavior in HIV-affected families. The more parents are mentally or physically ill, the more children become vulnerable to anxiety, depression, and highrisk behaviors [31,32]. This may lead to poor school performance, concentration issues, and general school failures [23,42,52]; (c) What, if any, psychological interventions have been conducted for HEU children?…”
Section: Discussionmentioning
confidence: 99%
“…Mental health resilience may be associated with multiple factors across children, family, and community. Child physical health, caregiving support, food security, peer relationship quality, and lower exposure to community violence and bullying or stigma seem to be strong predictors of resilience [31,32]. Moreover, a study that was carried out in Egypt suggests that children and adolescents of HIV-positive parents had a significantly lower health-related quality of life than children of healthy parents [33].…”
Section: Self-esteem and Resiliencementioning
confidence: 99%
“…Poverty and marginalization in sub-Saharian African countries easily result from engaging in problem behaviours (drug addition, gang activity, sexually aggressive behaviour, etc.) or being an easily victim of problem behaviours (Hensels et al, 2016; Small et al, 2019). Using an evidence-based approach with a visible structure, that gives immediate result, made students and school staff aware of the feasibility of the work.…”
Section: Methodsmentioning
confidence: 99%